IMPLEMENTATION OF AUGMENTED REALITY TECHNOLOGY BASED ANDROID TO DETECT AND FIND OUT LOCATION OF NEAREST GAS STATION IN BANDAR LAMPUNG CITY - Didik Kurniawan; Aristoteles Aristoteles; Muhammad Fathan Kurniawan (Jurnal Komputasi, 2015)
Augmented Reality (AR) is a term for an environment that combines real world and virtual world, where objects in real world can be recognized through the position, direction, and location. One of AR technology which is currently being developed is Markerless Augmented Reality, with this technology, users no longer need to use a marker to display digital elements. This technology can also be used to visualize information interactively, especially when this technology is integrated with mobile devices such as smartphones that have Android operating system. Camera feature, internet, accelerometer, digital maps and GPS (Global Positioning System) on Android devices can be integrated so that AR technology can be implemented. In this research, Markerless Augmented Reality technology is implemented to detect and find out the location of the nearest gas station in Bandar Lampung city. This application was designed and then implemented by using Java for Android programming language and Beyond AR framework to detect and display AR object and the Google Maps API to display a map of Â location of gas stations. The result of testing data using an Equivalence Partitioning testing indicates that the application can function in accordance with the analysis. Additionally, based on questionnaire data, this application is a user friendly application (with an average grade of 4.29 / Excellent) and interactive (with an average grade of 4.20 / Well).